2021
DOI: 10.1061/(asce)co.1943-7862.0002017
|View full text |Cite
|
Sign up to set email alerts
|

Systemic BIM Adoption: A Multilevel Perspective

Abstract: Systemic innovations require multiple interdependent actors to change their practices simultaneously in order to realise the benefits of the innovation. Building Information Modelling (BIM) has been classified as a systemic innovation that is adopted by building projects, firms, and users. However, the slow diffusion of BIM in the Architecture, Engineering, and Construction (AEC) sector has maintained the gap between BIM visions and actual BIM practice. Some governments are planning to enact policies to promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 63 publications
5
46
5
Order By: Relevance
“…Recent studies by Charlton et al. (2020) and Murguia et al. (2021) support the relevance of this premise, although their epistemological beliefs are similar to the premise they criticised.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Recent studies by Charlton et al. (2020) and Murguia et al. (2021) support the relevance of this premise, although their epistemological beliefs are similar to the premise they criticised.…”
Section: Introductionmentioning
confidence: 85%
“…Thus, it is apt to ask: what variables are relevant practically to explain the difficulties associated with executive choice to accept or reject BIM? Questions similar to this had been asked by Charlton et al (2020) and Murguia et al (2021). Because of the ill-structured nature, there are significant methodological challenges that associate with the assessment of acceptance of technological innovations, including the need for an innovative scale to assess user attitude (Shen et al, 2020;Ratchford and Ratchford, 2021).…”
Section: Processes Of Solution Incubationmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, based on the discussion of the complexity of BIM adoption, it is suggested that future studies investigate BIM post-adoption behaviors and analyze the environmental context's impact on BIM adoption, such as from the perspectives of policies, markets, organizations, emergencies, etc. The behaviors should be studied in a systemic manner, including both acceptance and resistance at the firm, project, and user levels [73]. Considering the interdependent and evolutionary nature of the behaviors, cross-cultural, cross-national, and longitudinal research should also be conducted [64].…”
Section: Future Research Directionsmentioning
confidence: 99%